ICOMOS International Cultural Tourism Charters 1976-2021: Evolution, Contributions and Trends in Cultural Heritage Protection - Martínez Yáñez, Celia (Protection of Cultural Heritage, 2022)
Since its establishment in the 1965, the standard setting texts produced by ICOMOS have become the most reputed, influential and distributed documents concerning cultural heritage protection worldwide. An examination of all ICOMOS charters and recommendations makes clear the indispensable role of this organisation to disseminating best conservation, restoration and management practices during the last sixty years. These recommendations also show the persistence of ICOMOS in tackling the numerous pressures that challenge heritage preservation around the world. Tourism is undoubtedly one of the most important and global of these pressures due to its considerable influence at all levels of cultural heritage management and decision-making. This paper analyses the early pioneering role of ICOMOS to promote responsible tourism. It does so through an evaluation of its international cultural tourism charters from 1976, when the first was adopted, up to 2021, when the ICOMOS has adopted the ICOMOS Draft International Charter for Cultural Heritage Tourism (2021): Reinforcing cultural heritage protection and community resilience through responsible and sustainable tourism management for its adoption at the ICOMOS General Assembly in Bangkok. The long process for drafting and approving this Charter and as well as its new conceptual approaches show the emerging trends that affect cultural heritage globally and faciliate broader reflection on the future of standard setting texts on this area.